A Discourse of Capital Punishment in the Islamic Law and Human Rights Law - Muhammad Eko Saputro; Andhika Febriansyah; Faradisya Diandra Putri (Contemporary Issues on Interfaith Law and Society, 2023)
The death penalty for convicts is an age-old subject to a lot of criticism from various quarters. The implementation of the death penalty is considered inconsistent with the principles of human rights which are principles of international law where countries cannot refuse because of common alignments, namely the right to life. The punishment of m ati raises pros and cons in Indonesian society, some agree with this punishment because the death penalty intends to protect the public interest and not a few oppose it, they argue that the death penalty is contrary to human  rights principles. This fact encourages the author to examine the implementation of the death penalty based on human rights and Islamic law, this is because the majority of Indonesians are adherents of the Islamic religion and also because the implementation of the death penalty is still carried out in Indonesia in certain crime cases. To examine this conflict, the author uses a normative juridical method with the conclusion that the death penalty is contrary to human rights because it eliminates the right to life for a person, but the implementation of the death penalty can be justified if the implementation of the death penalty is carried out in order to protect human rights and is also imposed on convicts who commit crimes beyond the limits stipulated in the legislation.